The poor have been raped’: An analysis of politicised collective identity in facebook groups against the financial crisis in Cyprus - Triga, Vasiliki; Papa, Venetia (My University, 2015)
This paper investigates the content of collective identities as constructed in Facebook groups created in protest against the haircut in 2013 in Cyprus. Given its supplementary role to offline social action, we use Facebook as a research domain and data gathering tool. Drawing on the concept of politicised collective identity we undertake a qualitative content analysis of the posts in three Facebook groups. The analysis reveals two main forms of collective identification. The first presents a rather common form of collective identity that is informed ideologically by nationalism. The second is built upon a strong anti-president rhetoric, echoing the arguments of the opposition parties. The ‘banal’ nature of such identities probably go a long way in accounting for the limited potential for collective action-unlike some of the other European crisis countries.
Keywords: Adversarial attributions; Civil society; Cyprus crisis; Facebook groups; Nationalism; Online social media; Politicised collective identities; Shared grievances; Social movements; Thematic analysis